(untitled) (Research, Society and Development, 2024)
Primary Care or Primary Health Care tend to achieve universal coverage in relation to the health system, as it presents a low-cost practice. Family Health Strategy, as a proposal for the reorganization of the care model, through the implementation of a multidisciplinary team in the Basic Health Units. The work of the team of health professionals accompanies the families inserted in the territory, implementing actions of recovery, rehabilitation of diseases and injuries with a focus on the promotion and prevention of community health. Objective: To analyze the role of nurses in the Family Health Strategy (FHS) in the literature. Methodology: Narrative review research of a qualitative nature and exploratory approach. Data collection was carried out on 2 public platforms: Virtual Health Library (VHL) and Scientific Electronic Library Online (SciELO). Results: After the treatment of data collected, 1 empirical category emerged that is part of this result, in which it identifies the textual organization in the period from 2019 to 2024, in which it appears author/year, journal and summary of the results found in 20 journals. Final Considerations: it was established that nurses have a relevant role in what is the responsibility of the Family Health Strategy (FHS) as attributions of planning, management, execution, supervising, evaluating individual or collective actions, nursing care and actions of promotion, prevention and rehabilitation of care in the process of Health and education.